Owners vs. managers: Disparities of attitudes on the business risk in SME segment - Ján Dvorský; Ludmila Kozubikova; Aleksandr Ključnikov; Eva Ivanova (Amfiteatru Economic Journal, 2022)
The article aims to identify disparities in the perception of business risks between the owners and managers of small and medium-sized enterprises (SMEs) in the V4 countries. The statements of strategic, market, personnel, legal and operational risks are the research's subject. Disparities of attitudes on the business risks were verified on the sample of 1585 SMEs by the mathematic method with the non-parametric approach - the Kruskal-Wallis test. The most significant disparities are in the perception of the adequacy of the market risk's level in the case of SMEs. The owners are significantly more optimistic in their market risk assessment than the managers of SMEs. On the other hand, the managers compared to the owners present a more pessimistic assessment concerning the statement that the business environment in their field of doing business is over-regulated. The respondents presented the same attitudes in the cases of the operational and personnel risk statements. Continuity of views and the perception of the business risks are critical factors for the growth of SMEs' business performance. Implications and consequences are generally valid for all SMEs, not only the ones from the V4 countries.
Keywords: M21; G32; L26; 330; SMEs; manager; business owner; business risks; case study; central European countries